Effect of different artificial shrinkage methods, when applied before blastocyst vitrification, on perinatal outcomes - Wang, Caizhu (Reprod Biol Endocrinol, 2017)
BACKGROUND: In recent years, single blastocyst transfer combined with vitrification has been applied widely, which can maximize the cumulative pregnancy rate in per oocyte retrieval cycles and minimize the multiple pregnancy rate. Thus, the guarantee for these is the effectiveness of vitrified blastocyst. Studies has shown that AS of the blastocoel cavity prior to vitrification can reduce injuries, increase the thawed blastocyst survival rate and implantation rate. Several AS methods have been established. However, only a few studies have compared the effectiveness and safety of these AS methods. In this study, we aimed to compare the clinical outcomes and neonatal outcomes in FET cycles with single blastocyst that were artificially shrunk before vitrification by either LAS or MNAS method. METHODS: A retrospective comparative study of FET cycles in infertile patients which were at our clinic between January 2013 and December 2014. These FET cycles were divided into two groups by the shrinking methods used before vitrification and the clinical and neonatal outcomes were assessed. RESULTS: There were no statistically differences in blastocyst survival rates (95.40% vs 94.05%, P > 0.05) between the LAS and MNAS groups. However, compared with MNAS, LAS improved the warmed blastocyst implantation/clinical pregnancy rate (60.82% vs 54.37%, P < 0.05), live birth rate (50.43% vs 45.22%, P < 0.05) and also increased the monozygotic twin rate (4.07% vs 1.73%, P < 0.05). There were no differences in the average gestational weeks (38.83 ± 1.57 vs 38.74 ± 1.75), premature birth rate (0.30% vs 0.49%), average birth weight (3217.89 ± 489.98 g vs 3150.88 ± 524.03 g), low birth weight rate (5.60% vs 8.63%) and malformation rate (0.59% vs 0.48%) (P > 0.05). CONCLUSIONS: No significant differences in neonatal outcomes were observed, while in clinical outcomes, LAS improved the warmed blastocyst implantation/clinical pregnancy rate and live birth rate markedly, there was also an increased risk of monozygotic twin pregnancies.